Financial Performance in Indonesian Banks: The Role of Ownership Structure, Dividend Policy, and Credit Risk - Ni Luh Nyoman Sherina Devi; I Kadek Bagiana (Philippine Social Science Journal, 2025)
This explanatory quantitative study analyzes the determinants of Return on Equity (ROE) for 47 Indonesian banks listed on the IDX from 2021 to 2023. Using multiple linear regression on 141 observations, the research evaluates the impact of managerial ownership, Dividend Payout Ratio (DPR), and credit risk (NPL). The findings reveal that managerial ownership has a positive, significant effect on ROE, affirming the benefits of incentive alignment, while credit risk negatively impacts profitability. Conversely, DPR showed no significant correlation, suggesting dividend policies in this sector are driven more by regulatory constraints than performance metrics. Ultimately, the study recommends that stakeholders prioritize managerial ownership and robust risk management over dividend indicators to optimize financial performance.